2022
DOI: 10.3390/pharmacy11010004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Outcomes: Acceptability of Medication Formulations for the Treatment of Acute Agitation in a Psychiatric Population

Abstract: BACKGROUND: There is limited research evaluating patient acceptability of medication formulations in the treatment of acute agitation. This study assessed patient acceptability of medication formulations (tablet, orally-dissolving-tablet [ODT], liquid, intramuscular injection [IM], inhaled device [INH]) for the treatment of acute agitation and examined correlating factors. METHODS: Adults with psychotic illness or bipolar disorder receiving emergency or inpatient services at an inpatient psychiatric facility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A recent study on patient’s acceptance of medication formulations for acute agitation found that there was a clear preference for oral formulations over intramuscular or inhaled formulations 15 . This finding is particularly important, as treatment guidelines now recommend that patient preferences are considered in treatment choices (shared decision-making or informed choice) 15 . A survey of hospitalized patients with schizophrenia in 2010 showed that 42% wanted to be involved in treatment decisions 15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study on patient’s acceptance of medication formulations for acute agitation found that there was a clear preference for oral formulations over intramuscular or inhaled formulations 15 . This finding is particularly important, as treatment guidelines now recommend that patient preferences are considered in treatment choices (shared decision-making or informed choice) 15 . A survey of hospitalized patients with schizophrenia in 2010 showed that 42% wanted to be involved in treatment decisions 15 .…”
Section: Introductionmentioning
confidence: 99%
“…This finding is particularly important, as treatment guidelines now recommend that patient preferences are considered in treatment choices (shared decision-making or informed choice) 15 . A survey of hospitalized patients with schizophrenia in 2010 showed that 42% wanted to be involved in treatment decisions 15 . Patients involved in their treatment decisions had a better therapeutic relationship, more positive attitudes towards their medication, and better insight than patients who were not involved 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant part of medication use in individuals with chronic conditions is their engagement in their care and their ability to be a part of the treatment decision-making process. Walker et al studied the need for patient input while choosing the medication formulation for acute agitation in behavioral emergencies [ 1 ]. Understanding these preferences and prescribing accordingly is critical to improving the acceptability of the medicine, medication adherence, and therapeutic alliance.…”
mentioning
confidence: 99%